2015
DOI: 10.1039/c5ra10494g
|View full text |Cite
|
Sign up to set email alerts
|

Excellent tribological and anti-corrosion performance of polyurethane composite coatings reinforced with functionalized graphene and graphene oxide nanosheets

Abstract: ABSTRACT: : : :In order to improve mechanical durability, polyurethane (PU) needs to be modified to enhance tribological and anti-corrosion properties. In this work, we fabricated a series of PU composite coatings reinforced with functionalized graphene (FG) and functionalized graphene oxide (FGO). The structural and morphological features of the composite coatings were characterized by Fourier transform infrared spectroscopy, Raman spectroscopy, X-ray diffraction, transmission electron microscopy and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(90 citation statements)
references
References 72 publications
0
72
0
1
Order By: Relevance
“…Therefore, Gr can play an essential role in improving the anticorrosion and antifriction properties of polymer coatings. Although a few studies have reported that the anticorrosion and antifriction properties of polymer coatings can be simultaneously altered using Gr additives [38][39][40], the Gr contents employed in those works were relatively low. Moreover, the COF of composite coatings used in those studies increased rapidly to a higher value (over 0.5) after a short sliding distance and the impedance modulus of the composite coatings at the lowest frequency in the Bode plot decreased with the passage of measurement time under immersion in 3.5 wt.% NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, Gr can play an essential role in improving the anticorrosion and antifriction properties of polymer coatings. Although a few studies have reported that the anticorrosion and antifriction properties of polymer coatings can be simultaneously altered using Gr additives [38][39][40], the Gr contents employed in those works were relatively low. Moreover, the COF of composite coatings used in those studies increased rapidly to a higher value (over 0.5) after a short sliding distance and the impedance modulus of the composite coatings at the lowest frequency in the Bode plot decreased with the passage of measurement time under immersion in 3.5 wt.% NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of Gr addition on the corrosion resistance of PU coatings, equivalent electric circuits were used to interpret the measured impedance data. In this study, equivalent electric circuits ( Figure 3) were employed to fit the measured Bode plots by using the ZSimpWin software [38,39,48]. R s denotes the solution resistance.…”
Section: Corrosion Resistance Of Pu/gr Composite Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The porosity value first decreased to the minimum of 2.7 × 10 −7 and then began to increase with the further decrease of Al mass fraction. With the decrease of the Al mass fraction from 40% to 30%, the state of Al particles changed from aggregation to uniform distribution, which may lead to a denser coating structure and decrease the porosity, thereby decreasing the NaCl solution penetration and increasing the corrosion resistance [24]. When the Al mass fraction was decreased from 30% to 10%, the morphology of the coating changed from the continuous particle contact state to the independent particle state, and thus the mixture was more loose (Figure 1).…”
Section: Corrosion Resistancementioning
confidence: 99%